Use of indocyanine green fluorescence guidance in redo ileocolic resection for Crohn's disease. (16th November 2021) - Freund, Michael R.; Kent, Ilan; Agarwal, Samir; Wexner, Steven D.
Abstract: Aim: Redo ileocolic resection in patients with Crohn's disease (CD) is associated with significant technical challenges that may be associated with high complication rates. The aim of this study was to evaluate the feasibility of near‐infrared fluorescence angiography with indocyanine green (ICG), often used to evaluate blood supply to the anastomosis in CD patients undergoing repeat ileocolic resection. Method: This study was a retrospective analysis of patients who underwent redo ileocolic resection using ICG bowel perfusion assessment between 2015 and 2021. Patients were matched and compared on a 1:2 basis with a control group undergoing the same procedure without perfusion assessment. Results: Twelve patients underwent redo ileocolic resection with ICG perfusion assessment (ICG group). These were compared with 24 patients who underwent the procedure without ICG (control group). Both groups were similar in demographics and operative characteristics including median operating time (255 vs. 255.5 min, p  = 0.39) and conversion rate (22% vs. 36.8%, p  = 0.68). Median estimated blood loss was significantly higher in the ICG group [150 (50–400) vs. 100 ml (20–125)]. Successful ICG perfusion assessment was seen in all patients in the ICG group and did not change management in any case. Overall postoperative complication rates were comparable between the groups (58.3% vs. 54.1%, p  = 0.72). No anastomotic leaks occurred in the ICG group compared with one (1/24, 4.2%) in the control group ( p  = 0.99). Conclusion: Fluorescence ICG perfusion assessment is feasible and safe in redo ileocolic resection in patients with CD. Larger studies are needed to evaluate whether this technique should be routinely used in these complex surgical interventions.